Determination of the neuropeptide Y in the adrenal cortex of stressed pregnant rats - Bertorello Cuenca, Magdalena (2015)
Chronic stress during pregnancy can alter many factors and mechanisms that maintain the homeostasis of the organism. Neuropeptide Y has anxiolytic functions and is involved in modulating the stress response. The aim was to determine the effects of chronic stress on the plasmatic corticosterone andestrogen levels and the immunolabeling of the neuropeptide Y in the adrenal cortex of pregnant rats. The immobilization stress was applied from the fourth day of gestation until the sacrifice at days 12, 17 and 21 of the gestation. Immunostaining techniques, radioimmunoassay, stereological analysis and quantification of images were used. In the stressed pregnant rats significant increase in the plasmatic corticosterone levels at 12, 17 and 21 days and in the plasmatic estrogen levels at 12 and 17 days were observed. On the other hand, a decrease in the INPY at 12 and 17 were observed. We can conclude that the increase in the plasmatic corticosterone and estrogen levels exerts aninhibitory effect on the adrenal neuropeptide Y immunostaining at 12 and 17 days of gestation.